Economic evaluation of a multimodal intervention in pre-frail and frail older people with diabetes mellitus: the MID-FRAIL project. (2nd January 2021) - Peña-Longobardo, Luz María; Oliva-Moreno, Juan; Zozaya, Neboa; Aranda-Reneo, Isaac; Trapero-Bertran, Marta; Laosa, Olga; Sinclair, Alan; Rodríguez-Mañas, Leocadio
ABSTRACT: Background : The aim of this study was to estimate the incremental cost-utility ratio (ICUR) of a multi-modal intervention in frail and pre-frail subjects aged ≥70 years with type-2 diabetes versus usual care group focused on quality adjusted life years (QALYs) in different European countries. Methods : The MID-FRAIL study was a cluster randomized multicentre trial conducted in seven European countries. A cost-utility analysis was carried out based on this study, conducted from the perspective of the health care system with a time horizon of one year. Univariate and probabilistic analysis were carried out to test the robustness of the results. Results : The cost estimation showed the offsetting health effect of the intervention program on total health care costs. The mean annual health care costs were 25% higher among patients in usual care. The mean incremental QALY gained per patient by the intervention group were 0.053 QALY compared with usual care practice. Conclusions : The MID-FRAIL intervention program showed to be the dominant option in comparison with usual care practice. It saved costs to the health care system and achieved worthwhile health gains. This finding should encourage its implementation, at least, in the trial participant countries.